Stochastic epidemics conditioned on their final outcome - White, Simon Richard (2010)
This thesis investigates the representation of a stochastic epidemic process as a directed random graph; we use this representation to impute the missing information in final size data to make Bayesian statistical inference about the model parameters using MCMC techniques.